Incidência Progressiva do ITCMD : uma política pública de combate à desigualdade social - Santos, Marinês dos (2016)
This research is a study on taxation of Tax Transfer by Death and Donation of Any Property and Rights (ITCMD), by State Government, in the free transfers of equity (inheritance and donation). The main focus is the analysis of the relation between taxation ate fixed rate (4%) and the process of social inequality, expressed in the urban area. In order to do so, we structured research in the following objectives: The fist one presents the debate on the taxation of ITCMD a fixed rate of 4% - as it is currently in Paraná. At this point is searched an approach theoretical with the subject of study. Talking into account assumption the use of a single rate in the taxation in free equity transmission reinforces a hierarchized social structure, segregated and unequal. The second objective is proposed to discuss the pattern of relationship between the capital and the urban social structure, modeled on the city of Maringa ? which we present a history of its origin and development. We conducted a review of existing bibliography, focusing on the analysis of the interference of the economic capital of existing bibliography, focusing on the analysis of the interference of the economic capital in the design of the structure of urban area. This interference which makes the urban area a place of inequality, segregation and class hierarchy ? a place that exposes the inequality of the society. In order to accomplish the third and final objective of the research it will be analyzed the free equity transmission occurred in the city of Maringa, in 2014. With this purpose the methodology consists of: a) a review of the chosen bibliography; b) empirical documental research which primary sources are the official documents (public deeds) of Notary Office and registration of the State Revenue and which secondary sources are data from Maringa obtained from the Census of the Brazilian Institute of Geography and Statistics (IBGE) in 2010. Finally ? at the end of the research ? to demonstrate the existence of a relation between the taxation of ITCMD and social inequality in the territory, we will use the Pearson correlation. For this statistical method we analyze a correlation between income variables, Heritage Received (inheritance/donation), and socio-occupational typology (Observatory of Metropolises, 2010). Evidence suggests that, taxing ITCMD with a fixed rate, increases social inequality, and that the opposite, applying progressive tax is a way of combating non-payment, the poverty and the social inequality. In other words, a public policy of the tax justice, that promotes social inclusion